An evidence-informed policymaking (EIPM) competency profile for the Brazilian Health System developed through consensus: process and outcomes - Jorge Otávio Maia Barreto; Davi Mamblona Marques Romão; Cecilia Setti; Maria Lúcia Teixeira Machado; Rachel Riera; Romeu Gomes; Daienne Amaral Machado; João Abreu; Keitty Regina Cordeiro de Andrade; Laura dos Santos Boeira; Letícia Pozza; Nathan Mendes Souza; et al. (BMC, 2023)
Abstract Background Evidence-informed policymaking (EIPM) requires a set of individual and organizational knowledge, skills and attitudes that should be articulated with background factors and needs. In this regard, the development of an EIPM competency profile is important to support the diagnosis, planning and implementation of EIPM. Purpose To present the process and outcomes of the development of an EIPM competency profile by an expert committee, to be applied in different contexts of the Brazilian Health System. Methods A committee of experts in EIPM shared different views, experiences and opinions to develop an EIPM competency profile for Brazil. In six consensus workshops mediated by facilitators, the committee defined from macro problems to key actions and performances essential for the competency profile. The development steps consisted of: (1) Constitution of the committee, including researchers, professionals with practical experience, managers, and educators; (2) Development of a rapid review on EIPM competency profiles; (3) Agreement on commitments and responsibilities in the processes; (4) Identification and definition of macro problems relating to the scope of the competency profile; and (5) Outlining of general and specific capacities, to be incorporated into the competency profile, categorized by key actions. Results The development of the EIPM competency profile was guided by the following macro problems: (1) lack of systematic and transparent decision-making processes in health policy management; (2) underdeveloped institutional capacity for knowledge management and translation; and (3) incipient use of scientific evidence in the formulation and implementation of health policies. A general framework of key actions and performances of the EIPM Competency Profile for Brazil was developed, including 42 specific and general key actions distributed by area of activity (Health Management, Scientific Research, Civil Society, Knowledge Translation, and Cross-sectional areas). Conclusions The competency profile presented in this article can be used in different contexts as a key tool for the institutionalization of EIPM.